Prevalence of Malnutrition Risk and the Impact of Nutrition Risk on Hospital Outcomes: Results From nutritionDay in the U.S. Issue 7 (22nd January 2019) - Sauer, Abby C.; Goates, Scott; Malone, Ainsley; Mogensen, Kris M.; Gewirtz, Gail; Sulz, Isabella; Moick, Sigrid; Laviano, Alessandro; Hiesmayr, Michael
Abstract: Background: Malnutrition risk estimates vary greatly, and no robust data on the association between food intake and outcomes exist for hospitals in the United States (U.S.). This study aimed to determine the prevalence of malnutrition risk and to evaluate the impact of food intake on mortality using the nutritionDay in the U.S. dataset. Methods: This study analyzed data from 2009 to 2015 for all adult patients from participating hospitals. Prevalence of malnutrition risk was determined by mapping self‐reported nutritionDay survey questions to the Malnutrition Screening Tool (MST). Fine and Gray competing‐risk analysis with clustering was used to evaluate the impact of nutrition risk and food intake on patients' 30‐day in‐hospital mortality, while controlling for age, mobility, and other disease‐related factors. Results: Analysis included data from 9959 adult patients from 601 wards. The overall prevalence of malnutrition risk (MST score ≥2) was 32.7%. On nutritionDay, 32.1% of patients ate a quarter of their meal or less. Hospital mortality hazard ratio was 3.24 (95% CI: [1.73, 6.07]; P ‐value < 0.001) for patients eating a quarter compared with those who ate all their meal and increased to 5.99 (95% CI: [3.03, 11.84]; P ‐value < 0.0001) for patients eating nothing despite being allowed to eat. Conclusion: This study provides the most robust estimate of malnutrition risk in U.S. hospitalized patients to date, finding that approximately 1 in 3 are at risk. Additionally, patients who have diminished meal intake experience increased mortality risk. These results highlight the ongoing issue of malnutrition in the hospital setting.